The Impact of Bureaucratic Reform Policy on Public Services at the Population and Civil Registration Service of North Padang Lawas Regency - Nasution, Adelina Fatmayanti; Sihombing, Marlon; Ridho, Hatta (PERSPEKTIF, 2024)
Based on an analysis of the bureaucratic conditions in North Padang Lawas Regency after more than 15 years as a new autonomous region, it appears that the quality of public services is still low. The evaluation of the Indonesian Ombudsman Representative for North Sumatra in 2021 placed the district in the "bad" category. Research using qualitative models highlights obstacles to change, including resistance from employees who want to maintain the status quo. Although there is increased work motivation among some employees, senior employees tend to stick to a conservative mindset, creating a lack of uniformity in bureaucratic behavior. Bureaucratic reform efforts appear to be producing positive results in Disdukcapil services. Simplification of bureaucracy, application of information technology, and increased accessibility increase efficiency and effectiveness. Even though the Community Satisfaction Index survey shows an increase in positive perceptions, there are still discrepancies with observations in the field, especially regarding slow processes and lack of employee understanding. In the face of conservative employee resistance, Disdukcapil leaders need to engage them more in the change process, involving them in decision-making. It is also important to ensure services are inclusive, considering the needs of people with physical limitations or limited access to technology. Solutions such as pick-up services or efficient physical services can be implemented. This improvement is important to achieve the goals of bureaucratic reform and provide better services to the community.